SIMULASI PENGUKURAN NILAI VISKOSITAS OLI MESRAN SAE 10 – SAE 40 DENGAN PENAMPIL LCD - Mujiman Mujiman (Universitas Ahmad Dahlan, 2008)
Factors viscosity and viscosity of the base oil is the amount of material that must be adapted to the classification engine. Thus the appropriate type of lubricating oil can be used according to the type, performance, and usage requirements. Machines working at high speeds require low viscosity values and vice versa. This study aimed to create a simulation tool to show the value of measuring viscosity oil with a control system that will execute the input data in the form of a timer to be used as viscosity units (km / ms)